Financial Statement Analysis to Assess the Financial Performance of the Government of South Nias Regency 2022–2024 - Tri Putrianis Laia; Irawan (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2026)
This study aims to analyze the financial performance of the Government of Nias Selatan Regency during the 2022–2024 fiscal years using the Value for Money approach. The research employs a descriptive qualitative method, utilizing secondary data in the form of Budget Realization Reports (LRA) obtained from the Directorate General of Fiscal Balance (DJPK), Ministry of Finance of the Republic of Indonesia. Financial performance is evaluated through six regional financial ratios: Degree of Decentralization, Expenditure Efficiency, Local Own-Source Revenue (PAD) Effectiveness, Regional Financial Independence, Expenditure Harmony, and Financial Growth. The results consistently indicate that the degree of decentralization falls into the “Very Low” category (below 3%), while the level of financial independence is classified as “Extremely Low,” placing the region in an instructive relationship pattern characterized by high dependence on central government transfers. Although PAD effectiveness increased significantly, reaching the “Highly Effective” category in 2024 (227.11%), this achievement was largely driven by the setting of revenue targets that were lower than the actual fiscal potential in the field. In terms of expenditure, financial management is considered “Inefficient” (above 84%) due to the tendency to fully absorb the allocated budget without meaningful savings. Furthermore, the budget structure remains unbalanced, as it is dominated by operational expenditures, while capital expenditure allocation consistently falls into the “Poor” category (below 20%). In conclusion, the fiscal capacity of Nias Selatan Regency remains unstable and requires reforms in budget planning as well as a reorientation toward capital expenditure allocation to foster sustainable regional economic independence.